Comparação entre os métodos de análise modal operacional e análise modal experimental a partir de um ensaio de vibração em uma estrutura frame - Angelino, Luan Roberto Marques (Universidade Federal de São Carlos, 2023)
Vibration sensors, such as accelerometers, are applied in various techniques for monitoring the structural health of structures, such as bridges, machines, among others. In modal analysis, there have been several studies using piezoelectric sensors with the aim of obtaining inherent properties of bodies, such as natural frequencies and mode of vibration. However, there are few studies validating the comparison between operational modal analysis and experimental modal analysis techniques. The purpose of this study, therefore, was to compare the frequency domain decomposition method, known as Operational Modal Analysis (OMA), with traditional modal analysis in a vibration test of an aluminum structure, representing a two-story building. Two PCB333B30 sensors were used for extracting acceleration data, and an impact hammer was used to excite the building. In order to compare the experimental methods, a finite element simulation was performed. Subsequently, the measurements underwent signal processing using Matlab, which allowed the extraction of resonance frequencies, modal shapes, and other information. The results showed a close proximity in the modes and frequencies obtained by both methods. However, due to the impact direction of the hammer, it was not possible to excite some of the vibration modes found in the finite element analysis. Consequently, it can be concluded that due to its ease of implementation and low setup costs, the operational modal analysis method is the most recommended for this structure.
Comparison between operational and experimental modal analysis methods on vibration testing of a frame structure
Keywords: Decomposição no domínio da frequência; Simulação de elementos finitos; Função de resposta em frequência; Vibração mecânica; ENGENHARIAS::ENGENHARIA MECANICA::MECANICA DOS SOLIDOS